Estimating the probability of forecasted events - Madera, Alexander (International Journal of Accounting and Economics Studies, 2016)
The article elaborates a method for estimating the probabilities of occurrence of prognosticated events in future. On the basis of the data from the previous periods about prognosticating the relevant events, as well as the data about the trends observed at present, two matrices are formed, the product of which is the matrix for the prognosis errors committed by the individual or the expert. The article shows that the vector for probabilities of the prognosticated events is the eigenvector of the prognosis error matrix, which corresponds to its single eigenvalue. Application of the elaborated method is shown on the definite example for forecasting demand of new products.